2008
DOI: 10.1002/pbc.21588
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and outcomes of medulloblastoma in adults

Abstract: Adult medulloblastoma has distinct characteristics from the pediatric population including presentation in the lateral cerebellar hemispheres. Late relapses, especially in the posterior fossa, are a significant problem. Further follow-up will be required to ascertain the effect of adjuvant chemotherapy on survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
23
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 34 publications
3
23
0
Order By: Relevance
“…Some investigators postulate that maturity of language and motor systems in older individuals makes them less vulnerable (21,(32)(33)(34). Differential tumor location in older groups may be a confounding factor (35)(36)(37)(38).…”
Section: Discussionmentioning
confidence: 96%
“…Some investigators postulate that maturity of language and motor systems in older individuals makes them less vulnerable (21,(32)(33)(34). Differential tumor location in older groups may be a confounding factor (35)(36)(37)(38).…”
Section: Discussionmentioning
confidence: 96%
“…GI toxicities are relatively common and when refractory to medication, can affect outcomes and quality of life(5, 12, 13). In this study, patients receiving p-CSI had significantly less weight loss, nausea/vomiting, and medical management of dysphagia when compared to x-CSI.…”
Section: Discussionmentioning
confidence: 99%
“…3 Recently reported overall survival rates for both children and adults are in the 60th and 70th percentiles, a significant increase from the 29% 5-year overall survival rate reported in earlier periods. 2,[4][5][6][7][8][9][10] Studies have demonstrated that medulloblastomas in adults and children are histologically and genetically different diseases. [11][12][13] Because of obvious differences in expected survival between adults and children in the general population (with adults more likely to die than children), comparing the survival profiles of children and adults with brain tumors requires a particular approach, namely, the use of relative survival.…”
Section: Introductionmentioning
confidence: 99%